LATE CRETACEOFS SEDIMENTARY ROCK IN BARITO BASIN, INDONESIA: LITHOLOGY, PALEONTOLOGY, AND PALEOENVIRONMENT - Akmaluddin Akmaluddin; Muhammad Virgiana A; Salahuddin Husein; Muhammad I. Novian; Nugroho I. Setiawan; Didit Hadi Barianto; Sunjaya E.S.; Banti T. Tampubolon (Testing Center for Oil and Gas LEMIGAS, 2019)
The Barito Basin so far known as back-arc basin that formed by the rifting in Early Tertiary, which the oldest sedimentary rock in this basin is believed has a Middle Eocene to Early Oligocene age. However, this research will present new evidence regarding the existence of sedimentary rocks that are older than Cenozoic age in the Barito Basin. This research was carried out on Bongkang-2 well, as the main data, and other five wells which have an indication of the discovery of Pre-Tertiary sedimentary rocks, which are generally located in the northern part of the Barito Basin. Integration of mud log data, petrography, paleontology, and dip-meter data, resulting the identification of lithology, age and depositional environment, and then interpretation of the paleoenvironment of the Barito Basin in the Late Cretaceous is carried out. Based on the analysis of data, it is show that Pre-Tertiary sedimentary rocks found in the six wells analyzed has Cenomanian age, which is indicated by the presence of large foraminifera fossils in the form of Sulcoperculina sp. and Orbitolina sp. in Bongkang-2, Hayup-1 and Hayup-3 wells, as well as palynomorph fossils in the form of Cicatrico- sisporites dorogensis, A. tricornitatus, Aquilapollenites sp., Distaverrusporites margaritus and Classopolis cf. classoides in Bagok-1 and Bagok-2 wells. In addition, based on lithological analysis, in the Bongkang-2, Hayup-1 and Hayup-2 wells lithology develops in the form of limestone, shale and sandstone, while in the Didi-1, Bagok-1 and Bagok-2 wells lithology develops in the form of shale with sandstone and pyroclastic – volcaniclastics rock intercalation. Then, based on the integration of lithology and paleontology analysis, it is known that in the Cenomanian age, terrestrial environments developed in the western part of the Barito Basin, while in the eastern part the shallow marine environment developed.